A Human-Rights Based Approach to the Economic Security of Older People in Moldova - Dávalos, María Eugenia (World Bank, Washington, DC, 2017)
The aging challenge in Moldova is pressing. The average age is rising at a much more rapid rate in Moldova than in neighboring countries, and the size of the population is shrinking. The demographic trends are driven by three factors: low fertility, high net emigration, and low life expectancy. Moreover, the risks to well-being are many and diverse among the elderly. For instance, Moldova is one of the few countries in the Eastern Europe and Central Asia region where the elderly are poorer than the average population. In addition, the elderly in rural areas are at particularly high risk of poverty, and have lower access to basic services. The objective of the report is, first, to explore the situation of Moldova's older population in relation to their right to economic security and, second, create knowledge that can inform policy options to guarantee an adequate standard of living for current and future cohorts of the elderly.